Transanal drainage tube for the prevention of anastomotic leakage after rectal cancer surgery: a meta−analysis of randomized controlled trials - Xia, Shijun; Wu, Wenjiang; Ma, Lijuan; Luo, Lidan; Yu, Linchong; Li, Yue (Frontiers in Oncology, 2023)
Abstract Background: Anastomotic leakage (AL) is a serious complication of anterior resection for rectal cancer. The use of transanal drainage tubes (TDT) during surgery to prevent AL remains controversial. Therefore, we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to determine the efficacy of TDT in reducing AL. Methods: Relevant data and studies published from inception until November 1, 2022, were retrieved from PubMed, Embase, and Cochrane Library databases to compare the incidence of AL after anterior resection for rectal cancer with and without TDT. Results: This meta-analysis included 5 RCTs comprising 1385 patients. The results showed that the intraoperative use of TDT could not reduce the incidence of AL after rectal cancer surgery (risk ratio [RR], 0.91; 95% confidence interval [CI], 0.52–1.59; p = 0.75). A subgroup analysis of different degrees of AL revealed that TDT did not reduce the incidence of postoperative grade B AL (RR, 1.18; 95% CI, 0.67–2.09; p = 0.56) but decreased the incidence of grade C AL (RR, 0.28; 95% CI: 0.12–0.64; p = 0.003). Further, TDT did not reduce the incidence of AL in patients with rectal cancer and a stoma (RR, 2.40; 95% CI, 1.01–5.71; p = 0.05). Conclusion: TDT were ineffective in reducing the overall incidence of AL, but they might be beneficial in reducing the incidence of grade C AL in patients who underwent anterior resection. However, additional multicenter RCTs with larger sample sizes based on unified control standards and TDT indications are warranted to validate these findings.